Imaging the lungs with computed tomography. - Hansell, D.M (IEEE Engineering in medicine and biology magazine)
Describes investigating structure-function relationships in lung disease with high-resolution CT. The diagnosis of lung diseases relies heavily on imaging, which can be broadly divided into projectional (for example, chest radiography) and cross sectional (for example, computed tomography) techniques. Most imaging in respiratory medicine is performed for purely clinical diagnostic reasons, but there is increasing interest in the use of the latest imaging techniques to unravel the pathophysiology of complex diffuse lung diseases. In this specific area, a variety of image processing techniques have been developed to aid the detection of lung abnormalities. It is not the purpose of this article to describe such techniques in detail but rather to survey the areas of clinical investigation in which they have been used. There is considerable overlap between image processing techniques that seek to identify and to quantify abnormalities of the lung parenchyma, but it is the accurate quantification of abnormal lung that is so crucial for the investigation of structure-function relationships in lung disease